Faktor-Faktor Organizational Citizenship Behavior (Studi Kementerian Sekretariat Negara Republik Indonesia) - Efendy Zain; Nazwirman Nazwirman; Fia Kamilia Nurul Utami (Universitas YARSI, 2018)
The research was conducted at the Ministry of State Secretariat of the Republic of Indonesia, which is under and responsible to the president and has the duty to provide technical and administrative support and analysis of government affairs in the state secretarial field to assist the President and Vice President in organizing state government. Samples were used as many as 31 respondents consisting of all employees of Financial Bureau. Quantitative research method with analysis using SPSS version 23. The purpose of research to know and analyze the influence of Personality, Spiritual Intelligence, and Organizational Climate to Organizational Citizenship Behavior (OCB). The result of the research indicates that Personality Variable has positive and significant effect to OCB where the value of t-value is 3.028 t-table 2.051. Spiritual intelligence variables have positive and significant influence on OCB, coefficient value of 0.319 has t-value of 3.398 t-table 2.051. Organizational climate variable has positive and significant effect to OCB has coefficient value 0,194 and t- value 2,263 t-table 2,051 and significant value 0,032 0,05. Personality variables, spiritual intelligence and organizational climate together have a significant effect on OCB. Where F- value is 24.488 F-table 2.96 with a significant level below 0.05 ie 0.000. One of the organizational values that must be embraced and developed within the Ministry is the value of honesty, which is an aspect of spiritual intelligence. And by putting forward ethics and morals for the creation of a good organizational climate. Employees always try their best to be able to work extra and maintain interaction and cooperation between teams and with colleagues in accordance with OCB behavior so reliable